Spatial Analysis of Urban Growth in Spain (1900-2001) - Julie Le Gallo; Coro Chasco-Yrigoyen (European Regional Science Association (ERSA), 2006)
The purpose of this paper is to improve the knowledge of the Spanish urban system. We study the evolution of population growth among the group of 722 municipalities included in the Spanish urban areas over the period from 1900-2001. Urban population cross-sectional distribution is characterized by means of nonparametric estimations of density functions, and the growth process is modeled as a first-order stationary Markov chain. A spatial SUR model is also estimated for the Zipf's law. Spatial effects are then introduced within the Markov chain framework using regional conditioning and spatial Markov chains.
Keywords: 330